What Causes Carbonates to Form “Shrubby” Morphologies? An Anthropocene Limestone Case Study - Bastianini, Laura; Rogerson, Mike; Mercedes-Martín, Ramon; Prior, Timothy J.; Cesar, Edgley A.; Mayes, William M. (Frontiers in Earth Science, 2019)
The South Atlantic Aptian “Pre-salt” shrubby carbonate Formations of Brazil and Angola are of major interest for the oil industry due to their potential hydrocarbon accumulations. Although the general sedimentology of these deposits is widely recognised to be within saline, alkaline lakes in rift volcanic settings, the specific genesis of shrubby carbonate morphologies remains unclear. This study reports the first petrographically comparable shrubby carbonates amongst other carbonate microfacies from an Anthropocene limestone formed under hyperalkaline (pH 9-12) and hypersaline (conductivity 425-3200µS) conditions at ambient temperature (12.5-13 oC) (Consett, UK). This discovery allows us to capitalise on exceptional long-term hydrochemical monitoring efforts from the site, demonstrating that shrubby carbonates occur uniquely within the waters richest in calcium (~240mg/L) and with highest pH (~12) and consequently with very high levels of supersaturation. However, the physical distribution of shrubs is more comparable with estimated local kinetic precipitation rate than it is to thermodynamic saturation, indicating that the fundamental control on shrub formation arises from crystal surface processes. The shrubby carbonate we report grows in the presence of significant diatomaceous and cyanobacterial biofilms, despite the highly alkaline conditions. These biofilms are lost from the deposited material early due to the high solubility of organic and silica within in hyperalkaline settings, and this loss contributes to very high intercrystalline porosity. Despite the presence of these microbes, few if any of the fabrics we report would be considered as “boundstones” despite it being clear that most fabrics are being deposited in the presence of abundant extra-cellular polymeric substances. We are aware of no previous petrographic work on anthropogenic carbonates of this type, and recommend further investigation to capitalise on what can be learned from these “accidental laboratories”.